1986
DOI: 10.1210/jcem-62-2-268
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Internalization and Degradation in Adipocytes from Normal and Type II Diabetic Subjects*

Abstract: We studied the ability of isolated adipocytes from normal and type II diabetic subjects to internalize and process [125I]insulin. Adipocytes were incubated with [125I]insulin at 16 or 37 C, and at various times total cell-associated, surface-bound, and intracellular insulin were quantitated using an acid-barbital extraction technique which quickly removes cell surface insulin, leaving behind the intracellular insulin. Insulin internalization was slow in normal adipocytes at 16 C, such that only 13% of total ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…Previous in vivo and in vitro investigations have provided substantial evidence for a relationship between insulin action and intracellular processing of insulin and its receptor (Ferrannini et al, 1982;Flier et al, 1982;Peavy et al, 1984;Veda et al, 1985;Jochen and Berhanu, 1987;Miller, 1988). Furthermore, it has been suggested that abnormalities in insulin receptor recycling and intracellular processing of the insulinreceptor complex might contribute to impair insulin action in patients with type 2 diabetes mellitus (Jochen et al, 1986;Grunberger et al, 1989;Trischitta et al, 1989;Benzi et al, 1990Benzi et al, , 1997Sesti et al, 1996). We found that treatment with glimepiride causes an increase in both insulin sensitivity and responsiveness for glucose incorporation into glycogen.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Previous in vivo and in vitro investigations have provided substantial evidence for a relationship between insulin action and intracellular processing of insulin and its receptor (Ferrannini et al, 1982;Flier et al, 1982;Peavy et al, 1984;Veda et al, 1985;Jochen and Berhanu, 1987;Miller, 1988). Furthermore, it has been suggested that abnormalities in insulin receptor recycling and intracellular processing of the insulinreceptor complex might contribute to impair insulin action in patients with type 2 diabetes mellitus (Jochen et al, 1986;Grunberger et al, 1989;Trischitta et al, 1989;Benzi et al, 1990Benzi et al, , 1997Sesti et al, 1996). We found that treatment with glimepiride causes an increase in both insulin sensitivity and responsiveness for glucose incorporation into glycogen.…”
Section: Discussionsupporting
confidence: 52%
“…Receptor-mediated insulin endocytosis is the principal mechanism for insulin clearance from the blood, and evi- dence has been provided that this process is impaired in patients with type 2 diabetes (Jochen et al, 1986;Grunberger et al, 1989;Trischitta et al, 1989;Benzi et al, 1990Benzi et al, , 1997. Thus, regulation by sulfonylureas of intracellular processing of insulin might have profound pathophysiological consequences by modulating the concentration of insulin in the peripheral circulation and avoiding the deleterious effects of hyperinsulinemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Jochen and coworkers reported that the amount of insulin internalized by a suspension of freshly isolated human adipocytes peaked after 30 min of incubation at 37°C. 15 By this time, 40% of the total insulin associated with the cells was internalized. After 60 min, the percentage of total cellassociated insulin within the cells dropped to 1.2%.…”
Section: Discussionmentioning
confidence: 95%
“…To date, a host ofcellular abnormalities have been described in NIDDM, including decreased binding of insulin to its receptor (1, 2, 5, 7-1 1), diminished rate of insulin receptor internalization (12), defects in the glucose transport system (1, 5, 9-11, 13, 14), and defects in the action ofintracellular enzymes (15). Whereas these alterations are part of the disordered carbohydrate and insulin metabo-lism observed in NIDDM, it is not clear that any of these defects represent a primary alteration.…”
Section: Introductionmentioning
confidence: 99%